Surveillance in the Digital Age - Nishnianidze, Anri (European Scientific Journal, ESJ, 2023)
Purpose: With technological progress, electronic devices have become available to almost all people. They use mobile phones, computing devices and other electronic devices every day for both personal and work purposes. The purpose of the research is to analyze how people are being monitored in the digital world and what is needed to protect citizens from mass surveillance. Design/methodology/approach: In the process of developing the research, using scientific methods, both the opinions of scientists about surveillance in the digital age and the past cases of mass surveillance of people’s actions in the digital world were analyzed. Findings: In the modern era, almost everyone uses devices for various purposes. Most often they use search engines, social networks, or other means of the digital world. But, they don’t realize that not every piece of data they put into cyberspace "disappears." The purpose of the study is to show how the said data is acquired, how they are used, and what dangers humanity is facing if people’s private life is not protected from surveillance in the digital age. Research limitations/implications: The research aims to analyze the existing scientific works, studies and articles about the dangers of surveillance in the digital age and to show the problems that exist in the process of fighting against surveillance. In the final part of the study, a minimum of recommendations will be presented, which are important to follow, so that the constitutional rights of people are not violated in the conditions of the possibility of simplified surveillance. Originality/value: There is hardly a person who does not use an electronic device to communicate in cyberspace. They use cyberspace for both work and personal purposes. In many cases, the data that is shared in cyberspace is not secured and through automated surveillance models, certain individuals, groups of individuals or states get hold of people’s data, thereby successfully conducting surveillance. Due to the mentioned reasons, the research is of special relevance and it is important to show the means of surveillance and the ways of fighting them to protect fundamental human rights in the digital age.